BENTUK TINDAK TUTUR PENOLAKAN PADA NOVEL "AYAT-AYAT CINTA" KARYA HABIBURRAHMAN EL SHIRAZY - Emma Maemunah (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
Refusal belongs to illocutionary acts of commissive. It occurs in all languages and is formulated differently based on their cultural background. People refuse either directly or indirectly. Beebe and Takahashi (1990) provided a classification of refusal strategy that can be used to analyze the form of refusal utterances. This study aims to discover the refusal strategies used in the novel of Ayat-ayat Cinta by Habiburrahman El Shirazy. The analysis was done to the speech act of refusals (SARs) in response to requests, questions, suggestions, orders, and invitations. The data were analyzed and categorized according to the refusal taxonomy by Beebe et al. To see the felicity condition of the refusal, the IFIDs are used to indicate the performative verbs of refusals utterances. The finding showed that the refusers perform different SARs. Indirect SARs of excuse/reason/explanation, statement of principle, and statement of regret were the prefered formula used in refusing. Besides, the power relation of the refusers which were higher, equal, and lower also distinguished the choice of semantic formula. The indirect SAR of flat no was not much prefered by the three power relation of the refusers. The performative verbs used in the refusal utterances are tell, ask, threaten, promise, request, inform, forbid, and beg.